The Effect of Inquiry-Based Learning on Students’ Writing Skills at Senior High School 1 Kampar Utara - Lina, Yola Rosa; Luthfi, Amir; Haris, Hannisa (Universitas Pahlawan Tuanku Tambusai, 2026)
Writing is a productive skill that involves expressing thoughts and ideas effectively in written form. However, mastering writing in English is often challenging. At SMA Negeri 1 Kampar Utara, students still face difficulties in developing clear and coherent text. It has been observed that the students struggle to organize ideas and construct well-structured writing. One of the contributing factors to these writing difficulties is the reliance on conventional teaching methods, such as the expository teaching method which tend to be teacher-centered, and result in low writing skill achievement. This study aims to investigate the effect of inquiry based learning on students' writing skill at SMA Negeri 1 Kampar Utara. Employing a quantitative quasi-experimental design, the research involved 52 students selected through a total sampling technique. The participants were divided into two groups : Class XI-1 as the experimental group class (26 students) and the Class XI-2 as the control group class (26 students). The sampling technique used was total sampling. The instrument of the research was writing test, data were collected though pre-test and post-test. The data analysis techniques include normality testing,homogeneity, and T-tests. The independent samples t-test obtained a t-value of 2.863 t-table 2.009 with significant value of p = 0.006 0.05, then H0 was rejected and Ha was accepted. These findings demonstrate that IBL produced a statistically significant effect on writing skill compared to the expository teaching method. Thus, inquiry-based learning significantly enhances students' writing skill at SMA Negeri 1 Kampar Utara.